A feasibility study on spirulina algaculture using photobioreactor - Andrade, Benedict Ivan; Carino, Miguel Isidro; Dela Costa, Katrina; Sze, Sherlaine
According to Euromonitor, Filipinos are in the state of adapting to a healthier lifestyle as health, nutrition and fitness is becoming a trend both locally and globally. Many of these are middle-aged Filipinos, who are predicted to further drive demand for vitamins and dietary supplements. Considered as 'the best food for the 21st century" by WHO, Spirulina promises huge growth as its demand growth is at 30%. One tablet is equivalent to 500 grams of vegetables. It is a rich source of protein and many other functional nutrients and is deemed a great aid in improving the nutritional state of many Filipinos. Lumos Technology, the country's champion for the Super Food, SpirulinaPlatensis, offers its customers all-natural 100% pure, safe, technologically-grown, full and nutritionally packed Spirulina Tablets - the company's complete answer to the long list of health, fitness, and nutritional needs of the Filipino consumer. While other Spirulina providers create Spirulina in open ponds, which may leave room for contamination, Lumos Technology guarantees superior quality by processing the Spirulinaplatensis in a unique photobioreactor process and is then dried, ground, pressed and packaged into tablet form. Processed by technologies that are efficient and effective, each Spirulina pack and tablet is assured of its qualityó100% natural, 100% Spirulina and 100% safe to use with no outside contamination. The culture method for algae production is by growing SpirulinaPlatensis on a closed vessel. The temperature, PH, salinity and growth rate of which is more controlled, ensuring maximum growth of nutrients for each Spirulina cell. The target market is Filipinos in social classes A and B and who are in their late 30's to 60's. This segment is considered as the biggest segment with 20 Million in population. The growing population and the increase in disposable incomes for this segment are strategic for Lumos. Furthermore, the product will strengthen its presence in the market by being the first to enter in popular retail stores like Mercury Drug Store and Watsons while selling at PhP 1,199 per bottle to take advantage of the perceptions of quality. With total forecasted revenues of P 65,993,215 for the next five years of operation, LumosSpirulina proves to have high market feasibility. The innovation behind the superfood is its process. Various studies have testified the efficiency of the LED and the quality of using a photobioreactor. In terms of areal productivity, a photobioreactor system can produce 17 times more than an open pond system. Furthermore, a study conducted by Elvis Chua, et al, concluded that the use of alternating blue and red LED light sources will result to a yield of 20% more than the normal photobioreactor. Lumos aims to grow the spirulina in its LED-sourced photobioreactor in 3 days.The technology and the corresponding initial costs in producing the product are technically feasible. The result of the financial analysis proves the financial feasibility of Lumos Technology. The net present value of Lumos is positive with a total net income of P18,295,709 for the five years. A total initial investment of just P 11,013,265 for the project which will be financed by full equity and investment of 3 Million by potential investors, promises payback in three years. Moreover, the profitability ratios meet the standards shared by successful companies. Lumos will offer a product that aims to promote greater health and wellness of Filipinos. The results of the study show that this endeavor is feasible.